Cognitive symptoms after COVID-19 - M. Altuna; Mª.B. Sánchez-Saudinós; A. Lleó (Neurology Perspectives, 2021)
Introduction: SARS-CoV-2 infection frequently causes neurological symptoms. Cognitive alterations are among the most frequent symptoms, and may persist beyond the acute phase of infection. Methods: We conducted a narrative review of the literature. Results: Hospitalised patients, and especially critically ill patients, are at greater risk of developing cognitive symptoms. Post–COVID-19 cognitive symptoms, unlike those associated with other viral illnesses, have been observed in patients with mild infection, and present some atypical features. Cognitive symptoms may last longer in COVID-19 than in other infectious processes, and more frequently affect young people. Post–COVID-19 cognitive symptoms share common features with those described in chronic fatigue syndrome, including a similar profile with affective symptoms. Brief screening tests for cognitive impairment present suboptimal diagnostic performance, and standardised criteria are needed to ensure correct diagnosis.Post–COVID-19 cognitive impairment can have a significant impact on the patient's quality of life and functional independence, regardless of other post–COVID-19 symptoms. Currently, no specific treatments have been approved for post–COVID-19 cognitive impairment, although cognitive stimulation may be useful in some patients. Conclusions: Post–COVID-19 cognitive symptoms are common and are often associated with other systemic symptoms. Neuropsychological evaluation may be useful for diagnosis and to quantify their severity and long-term prognosis. Detailed, and individualised assessment of cognitive impairment may enable the design of treatment plans. Resumen: Introducción: La infección por SARS-Cov2 con frecuencia causa síntomas neurológicos. Los síntomas cognitivos se encuentran entre los síntomas más frecuentes y pueden persistir más allá de la fase aguda de la infección. Metodología: Revisión narrativa de la literatura. Resultados: El riesgo de padecer síntomas cognitivos es mayor en pacientes hospitalizados, especialmente en pacientes críticos. Los síntomas cognitivos post-COVID, a diferencia de los que aparecen en otros cuadros virales, se han observado en pacientes con infección leve y presentan algunos rasgos atípicos. La duración de la sintomatología cognitiva puede ser superior a otros procesos infecciosos y afectar con mayor frecuencia a personas jóvenes. Los síntomas cognitivos post-COVID comparten rasgos comunes con los descritos en el síndrome de la fatiga crónica, incluyendo un perfil similar de síntomas afectivos asociados. Los tests rápidos de cribado de deterioro cognitivo tienen un rendimiento diagnóstico subóptimo y son necesarios criterios estandarizados para un correcto diagnóstico.El deterioro cognitivo post-COVID puede ocasionar un impacto significativo en la calidad de vida y en la autonomía funcional del paciente, de forma independiente al resto de síntomas post-COVID. En la actualidad no existen tratamientos específicos aprobados para el deterioro cognitivo post-COVID, aunque la estimulación cognitiva puede ser útil en algunos pacientes. Conclusiones: Los síntomas cognitivos post-COVID son frecuentes, y con asiduidad se asocian a otros síntomas sistémicos. Una evaluación neuropsicológica puede ser de utilidad para el diagnóstico y para cuantificar su severidad y pronóstico a largo plazo. Una caracterización detallada e individualizada del deterioro cognitivo permite establecer medidas de tratamiento.